Algorithm for estimating the required flexible capacity reserve of the power system - Denis Y. Losev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: the increasing share of renewable energy sources, characterized by high variability and low predictability of their output, imposes new requirements on the reliability and stability of electric power systems. Significant power fluctuations of wind and solar power plants lead to an increase in the amplitude and frequency of deviations in the power balance, which necessitates the availability of sufficient flexible reserve capacity to enable rapid response to changes in load and generation. Existing methods for estimating reserve capacity often rely on averaged forecasts or static characteristics of the power system, which reduces the accuracy of determining flexibility needs under the increasingly complex structure of the energy balance. In modern power systems, there is a need to develop algorithms capable of accounting for the dynamic properties of the grid, the probabilistic nature of renewable energy operation, and integrating data from system operational dispatching. Developing an algorithm for determining the required flexible reserve capacity is an important step toward improving power supply reliability, optimizing the operating modes of generating equipment, and reducing operational costs. The development of such algorithms is particularly relevant for countries that are actively deploying renewable energy and modernizing their energy infrastructure. Therefore, the proposed study addresses one of the key challenges of modern electric power engineering and possesses high scientific and practical significance. Aim: development of an algorithm for estimating the required flexible capacity reserve of power systems considering variable generation from photovoltaic and wind power plants, as well as daily fluctuations in electricity consumption. Methods: there were used statistical methods of analysis and forecasting. Results: the hourly required flexible capacity reserves necessary to maintain the power balance of the electric power system under variable generation from renewable energy sources and demand have been determined.